Timing of surgery in acute burn care: A multicentre registry-based cohort study - Roos F.C. Salemans; Denise van Uden; Ymke Lucas; Anouk Pijpe; Eelke Bosma; Esther Middelkoop; Michiel H.J. Verhofstad; Margriet E. van Baar; Cornelis H. van der Vlies (Burns Open)
Early excision and grafting are standard care for severe burns, though implementation varies globally. In the Netherlands, surgery for moderate and severe burns tends to be relatively late. This study analysed the timing of surgery in Dutch burn care by examining patient, injury and treatment characteristics, and clinical outcomes. A multicentre registry-based cohort study was conducted using data from the Dutch Burn Repository R3 (2009–2021), including adult patients who underwent surgery at a Dutch burn centre. The primary outcome was surgical timing, with patients classified into early (≤7 days) and late surgery (>7 days) groups. Multivariable logistic regression identified predictors of early surgery, while trends in timing were assessed with quantile regression. The median time to surgery was 14 days (Q1–Q3: 9.0–19.0), with 670 of 3291 patients receiving early surgery (20 %). Surgical timing increased slightly over the 13-year period. Predictors of early surgery included older age, larger total body surface area burned, psychiatric medical history, and flame, flash, and contact burns compared to scald burns. This study underscores the nuanced Dutch policy regarding surgery and the influence of burn severity on surgical timing. Further research is needed, focusing on patient-centred outcomes and international perspectives.